1945-1974 гг. как период формирования советской историографии Ялтинской конференции - Шевченко, О.К. (Культура народов Причерноморья, 2013)
В статье исследуются вопросы освоения советской историографией Крымской
(Ялтинской) конференции 1945 г. Формулируются ключевые принципы советской исторической школы
определяются основополагающие предпосылки исторического анализа события.
Ключевые слова: советская историография, Крымская конференция, хронология. У статті досліджуються питання осягнення радянською історіографією Кримської
(Ялтинської) конференції 1945 р. Формулюються ключови принципи радянської історічної школи,
грунтовно аналізуються передумови історичного аналіза події.
Ключові слова: радянська історіографія, Кримська конференція, хронологія. The paper studies the issues of development of Soviet historiography of the Crimean (Yalta)
Conference in 1945 formulated the key principles of the Soviet historical school. Definitely just four principles:
1. A detailed study of the documents.
2. The style of the professional journalist. Ssozdanie vivid images.
3. An integrated approach to the Yalta Conference.
4. The purpose of the analysis - the help of Soviet diplomacy.
Chronology of Soviet historiography of the Yalta Conference. 1945-1954 years of birth of the Soviet historical
school "Yalta". 1955-1974 - is the formation of the Soviet approach, the emergence of the first collections of
documents, memoirs and monographs. 1975-1984 - development. The mass publication of documents,
publication of the memoirs of all the main, the emergence of schools and movements in one of the Soviet
approach. 1985-1991 - the culmination. Building strong foundations for the development of schools and
approaches the completion of the analysis of the historiography of the West, the publication of monographs.
Carrying a large scientific forum of experts on Soviet historians of the Yalta Conference.
In the first two periods of the development of Soviet historiography These following scientists: AS Erusalimskiy
and SB Sossinski. Much attention udelyaetsya analysis of the relationship of memoirs, documents and analytical
work (theses, newspaper articles,monographs).
Keywords: Soviet historiography, Yalta Conference, the chronology.